Insolvency Regimes, Technology Diffusion and Productivity Growth Evidence from Firms in OECD Countries - Adalet McGowan, Müge (OECD Publishing, 2017)
This paper explores the link between the design of insolvency regimes across countries and laggard firms' multi-factor productivity (MFP) growth, using new OECD indicators of the design of insolvency regimes. Firm-level analysis shows that reforms to insolvency regimes that lower barriers to corporate restructuring are associated with higher MFP growth of laggard firms. These results are consistent with the idea that insolvency regimes that do not unduly inhibit corporate restructuring can incentivise experimentation and provide scope to reconfigure production and organisational structures in order to faciliate technological adoption. The results also highlight policy complementarities, with insolvency regimes that reduce the cost of entrepreneurial failure potentially enhancing the MFP gains from lowering administrative entry barriers in product markets. Finally, we find that reducing debt bias in corporate tax systems and well-developed venture capital markets are associated higher laggard firm MFP growth, suggesting that equity financing can also be an important driver of technological diffusion. These findings carry strong policy implications, in light of the fact that there is much scope to reform insolvency regimes in many OECD countries and given evidence that stalling technological diffusion has contributed to the aggregate productivity slowdown
Keywords: Economics